Interspecific Variation in Nematode Responses to Metals. (29th March 2020) - Heaton, Andrew; Faulconer, Elizabeth; Milligan, Emma; Kroetz, Mary B.; Weir, Scott M.; Glaberman, Scott
Abstract: Performing toxicity testing on multiple species with differing degrees of evolutionary relatedness can provide important information on how chemical sensitivity varies among species and can help pinpoint the biological drivers of species sensitivity. Such knowledge could ultimately be used to design better multispecies predictive ecological risk assessment models and identify particularly sensitive species. However, laboratory toxicity tests involving multiple species can also be resource intensive, especially when each species has unique husbandry conditions. We performed lethality tests with 2 metals, copper chloride and zinc chloride, on 5 different nematode species, which are nested in their degree of evolutionary relatedness: Caenorhabditis briggsae, Caenorhabditis elegans, Oscheius myriophila, Oscheius tipulae, and Pristionchus pacificus . All species were successfully cultured and tested concurrently with limited resources, demonstrating that inexpensive, multispecies nematode toxicity testing systems are achievable. The results indicate that P. pacificus is the most sensitive to both metals. Conversely, C. elegans is the least sensitive species to copper, but the second most sensitive to zinc, indicating that species relationships do not necessarily predict species sensitivity. Toxicity testing with additional nematode species and types of chemicals is feasible and will help form more generalizable conclusions about relative species sensitivity. Environ Toxicol Chem 2020;39:1006–1016. © 2020 SETAC